Male Sprague-Dawley Rats Exposed to In Utero Di(n-butyl) Phthalate: Dose Dependent and Age-related Morphological Changes in Leydig Cell Smooth Endoplasmic Reticulum. (October 2013) - Shirai, Masaru; Wakui, Shin; Wempe, Michael F.; Mutou, Tomoko; Oyama, Noriko; Motohashi, Masaya; Takahashi, Hiroyuki; Kansaku, Norio; Asari, Masao; Hano, Hiroshi; Endou, Hitoshi
When 100 mg/kg/day of di( n -butyl) phthalate (DBP) was intragastrically administered to pregnant Sprague-Dawley rats throughout gestation days 12 to 21, the male pups had similar body weights with no apparent physical differences (e.g., litter size, sex ratio) compared to that of the vehicle group. However, prominent age-related morphological alterations in the smooth endoplasmic reticulum (sER) of testicular Leydig cells (LCs) were observed once these animals reached puberty. At weeks 5 to 7, the abundant sER with non-dilated cisternae was distributed in LCs. Subsequently, although the number of LCs significantly increased, the amount of sER was significantly decreased at 9 to 14 weeks of age and had disappeared at 17 weeks. In contrast, the number of LCs and the amount of sER in LCs of the lower dose groups (10, 30, and 50 mg/kg/day) were similar to those of the vehicle group. Further, serum testosterone levels in the 100 mg/kg dose group were significantly lower during 5 to 17 weeks of age. While their luteinizing hormone (LH) level was significantly lower at 5 to 7 weeks of age, it became significantly higher during 9 to 17 weeks. The amount of sER in LCs decreased with age with the increase in LCs proliferation and serum LH levels in rat exposed in utero to DBP in a dose-dependent manner.